Halal Certification and Its Relationship to Business Value: A Perspective of Fish Salting SMEs - Christian Michael; Yulita Henilia; Gularso Kurnadi; Wibowo Suryo; Marisa Muzammil Oktafalia; Sunarno (E3S Web of Conferences)
Small and medium-sized fish salting enterprises are the focus of this study, which also looks at the benefits and challenges of halal certification and its relationship to business value. Applying the observation method and statistical and descriptive research approaches, the study identifies a lack of knowledge, budgetary constraints, and inadequate aid from stakeholders as the three main obstacles that these small and medium enterprises (SMEs) confront. Despite these limitations, the study highlights the potential of halal certification to improve product quality, boost customer confidence, and increase market competitiveness, particularly in relation to the growing Muslim consumer market. Halal certification can provide significant advantages; not only does it ensure compliance with Islamic dietary requirements and cater to the growing Muslim market, but it also improves product quality, instils consumer trust and loyalty, and boosts market competitiveness. The study’s theoretical value enhances the knowledge-attitude-behavior model paradigm. Realistically, it lays out the steps that local SMEs may take to become certified and reap the benefits of doing so. Despite the study’s regional emphasis, its suggestions are generalizable to other areas. Future studies should investigate the financial performance of halal-certified and non-certified fish-salting enterprises, for instance.